Using Weibo and WeChat social media channels to assess public awareness and practices related to antimicrobial resistance, China, 2019 - Lei Wang; Sujian Situ; Jeanette J. Rainey; Bin He; Xiaoge Su; Ronald L. Moolenaar; Ying Cui (BMC, 2021)
Abstract Background Antimicrobial resistance (AMR) is a global healthcare problem, including in China where high rates of resistance to common bacterial infections have been documented. In 2016, the National Health and Family Planning Commission (NHFPC) in China established a comprehensive strategic plan to increase awareness about AMR through education programs. Methods We conducted an online survey to assess changes in public knowledge, awareness and practices related to AMR in China since 2016. The survey was administered using China's national and provincial level 12320 Health Hotline Weibo (micro-blog site) and WeChat (text messaging service) social media accounts from April 12, 2019 to May 7, 2019. All persons ≥16 years of age able to read Chinese were eligible to participate. Results A total of 2773 respondents completed the survey. Of the 2633 respondents indicating recent use of antibiotics, 84% (2223) reported obtaining their course of antibiotics from a hospital or pharmacy, 9% (246) of respondents reported using antibiotics saved from a previous prescription or treatment course, and 42% (1115) of respondents reported that they had stopped taking antibiotics as soon as they started feeling better. Most respondents correctly indicated that antibiotics can effectively treat urinary tract infections (86% [2388]) and skin infections (76% [2119]), but many incorrectly indicated that antibiotics can also treat viral infections such as measles (32% [889]) or a cold or flu (26% [726]). Of all respondents, 95% (2634) had heard of 'antibiotic resistance'. Almost half (47% [1315]) reported using antibiotics within the last 6 months. Conclusion While awareness of AMR was high in this survey of social media users in China, inappropriate antibiotic use remains common, including the believe that antibiotics can effectively treat viral infections. Multiple interventions targeting the correct use of antibiotics and information on the cause AMR are likely needed. The 12320 Health Hotline provides a platform for conducting routine surveys to monitor antibiotic use and knowledge about AMR.